2011
DOI: 10.1001/archdermatol.2011.109
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence After Treatment of Nonmelanoma Skin Cancer

Abstract: To determine long-term tumor recurrence rates after treatment of primary nonmelanoma skin cancer (NMSC). Data are currently insufficient to permit evidence-based choices among treatments for NMSC.Design: Prospective study of an inception cohort observed for a median of 6.6 years after treatment.Setting: Dermatology clinic at a Veterans Affairs hospital. Care was provided by dermatology resident or attending physicians.Patients: Consecutive sample of all 495 patients with 616 primary NMSCs diagnosed in 1999 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
73
2
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 94 publications
(84 citation statements)
references
References 16 publications
6
73
2
3
Order By: Relevance
“…In both subroups, men were more In the present study, 4.1% of all BCC lesions and 1.8% of all SCC lesions locally recurred dur ing the 7.5-years period, roughly agree ing with the observations from previous studies [27][28][29][30]. However, as they represented only microscopically verified cases, a certain number of tumor relapses could have been subsequently treated non-invasively without histopathologic examination.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…In both subroups, men were more In the present study, 4.1% of all BCC lesions and 1.8% of all SCC lesions locally recurred dur ing the 7.5-years period, roughly agree ing with the observations from previous studies [27][28][29][30]. However, as they represented only microscopically verified cases, a certain number of tumor relapses could have been subsequently treated non-invasively without histopathologic examination.…”
Section: Resultssupporting
confidence: 91%
“…The recurrence rate depends on several factors, such as anatomic location and size of lesions, histologic subtypes of tumors, chosen therapeutic modality and resection margin status after total surgical ex cision. According to literature data, local recurrence rates range between 3.4 and 4.3% for BCCs [27,28] and between 2 and 3.6% for SCCs [27,29,30]. These values are similar and even some authors [27] did Regard ing gender, we found that SCCs more frequently occurred in men (68.2%) than women (31.8%), justify ing data from many previous reports [1,11,12,17,18].…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Standart eksizyon 5 yıllık rekürrens oranlarının %2-10 arasında değiştiği bütün primer BHK olgularda etkili tedavi seçeneğidir [20][21][22] . Genel kabul gören güvenli cerrahi sınır 3-5 mm.…”
Section: Bhk Tedavi Seçenekleri Ve Güncel Yaklaşımlarunclassified
“…8,9 Currently, an estimated 1.5 million surgeries are performed every year for nonmelanoma skin cancers (both BCCs and squamous cell carcinomas), with treatment costs of about $2 billion. 10 Mohs surgery is labor-intensive, time-consuming, and expensive.…”
Section: Introductionmentioning
confidence: 99%